True-bone-ceramics / type I collagen scaffolds for repairing osteochondral defect - Yuhan Jiang; Tenghai Li; Yingyue Lou; Bingzhang Liu; Yilin Liu; Tian Li; Duo Zhang (Journal of Materials Science: Materials in Medicine)
Abstract In recent years, the incidence of cartilage defects has increased dramatically, and its etiology is complex and varied. Osteochondritis dissecans (OCD), as one of the main etiologies, damages both cartilage and bone tissues and can progress to severe osteoarthritis, which has been one of the difficult problems for clinicians. The vigorous development of material science and tissue engineering provides new ideas for the treatment of OCD, in which the selection of scaffold materials is particularly important. In this study, true-bone-ceramics (TBC), which has good mechanical strength and osteoconductivity, and type I collagen (COL1), which has excellent biocompatibility, were chosen as scaffold materials to co-construct the TBC/COL1 scaffold for osteochondral repair. In order to ensure the most appropriate collagen coating concentration, three experimental groups (1, 5, 12 mg/ml) were set up. Through the physicochemical property test, biocompatibility analysis and in vivo implantation experiments of composite scaffolds, 12 mg/ml TBC/COL1 scaffolds present the best repair effect among the three groups. Graphical Abstract